2020
DOI: 10.31219/osf.io/zu8fv
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fixel-based Analysis of Diffusion MRI: Methods, Applications, Challenges and Opportunities

Abstract: Diffusion MRI has provided the neuroimaging community with a powerful tool to acquire in-vivo data sensitive to microstructural features of white matter, up to 3 orders of magnitude smaller than typical voxel sizes. The key to extracting such valuable information lies in complex modelling techniques, which form the link between the rich diffusion MRI data and various metrics related to the microstructural organisation. Over time, increasingly advanced techniques have been developed, up to the point where some … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 0 publications
0
32
0
Order By: Relevance
“…Diffusion image processing. We performed FBA using MRtrix3 (http://www.mrtrix.org/), as previously described (18). Standard preprocessing was performed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Diffusion image processing. We performed FBA using MRtrix3 (http://www.mrtrix.org/), as previously described (18). Standard preprocessing was performed.…”
Section: Methodsmentioning
confidence: 99%
“…We used slacklining as the whole-body dynamic balance task, as previously reported (6). We also analyzed the gray and white matter microstructure related to each participant's initial balance capability with VBM using T1-weighted images and a newly developed fixel-based analysis (FBA) using diffusion-weighted images (17,18). Furthermore, as previous studies have indicated that 1-2 h of acute motor practice may induce structural changes in the white and gray matter, we investigated whether 30 min of dynamic balance training could induce structural changes (13,19).…”
mentioning
confidence: 99%
“…In a recent study we could also demonstrate that the segmental analysis of diffusion tensor imaging (DTI) derived metrics, such as fractional anisotropy (FA) and apparent diffusion coefficient (ADC), correlated with clinical outcomes ( 5 ). Here, we now set out to investigate whether more complex metrics derived from constrained spherical deconvolution (CSD) and probabilistic tractography, which allow for more detailed analysis of the white matter, would prove superior in terms of detecting tumor induced white matter (WM) changes ( 6 ). In this context we analyzed the structural impact of gliomas affecting the corticospinal tract (CST) in 65 patients.…”
Section: Introductionmentioning
confidence: 99%
“…An estimated 90% of voxels contain crossing fibers, which make it difficult to accurately interpret DT‐based analyses, as changes at the microstructural level may be undetected or misinterpreted due to a lack of fiber specificity. FB metrics have higher sensitivity than voxel‐wise DT metrics in detecting group‐wide differences in white matter (Dhollander et al, 2020). We also used meticulous tract‐extraction methods based on previously‐published methods (Kaur et al, 2014; Parikh et al, 2019; Teli et al, 2018) and our own systematic, iterative process.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown the improved sensitivity and specificity of CSD‐based tractography for detecting differences in white matter diffusion characteristics, when compared to DT‐tractography (Auriat, Borich, Snow, Wadden, & Boyd, 2015; Jeurissen, Leemans, Jones, Tournier, & Sijbers, 2011; Reijmer et al, 2012). CSD is valuable in group studies; by using a single response function to compute fODs for all subjects, population‐wide differences in diffusivity can be detected (Dhollander et al, 2020; Raffelt et al, 2012).…”
Section: Introductionmentioning
confidence: 99%